(untitled) (Journal of Hama University, 2024)
This research aims to evaluate the safety and efficacy of tramadol in combination with half the effective dose of xylazine and ketamine used, and its effect on some clinical indicators and hematological parameters in Bitches undergoing ovariectomy. The research was conducted on 12 clinically healthy (without progeny) bitches. A age (7-16) months and weight (9-17) kg, the animals were divided into tow groups (n=6 per group). The first group (Xylazine, Ketamine) injected xylazine 2 mg/kg and ketamine 5.5 mg/kg intramuscularly, and the second group (Tramadol, Xylazine, Ketamine ) injected tramadol 4 mg/kg and xylazine 1 mg/kg and ketamine 2.5 mg/kg intramuscularly. Duration of operation (46.00±3.72) minutes. We found the time onset of anesthesia (5.0±0.0/ 4.0±0.63) minutes, duration of surgical anesthesia (42.33±5.82/ 70.0±11.17) minutes, and duration of analgesia (48.33±9.11/ 242.0±40.20) minutes in the first and second groups, respectively.The results of clinical indicators showed in the first group, a significant decrease in heart rate, respiratory rate and rectal temperature during the times (15-30-60-120) minutes postoperative, and a significant increase in the capillary refill time during the time (15-30-60-120) minutes postoperative. In the second group, a significant decrease in heart rate, respiratory rate and rectal temperature during the times (15-30-60) minutes postoperative, and a significant increase in capillary refill time during the times (15-30-60) minutes postoperative, at the significance level P≤ 0.05. The results of hematological parameters showed in the first group, a significant decrease in (RBC), (PLT), (Hb) and (PCV) during the times (15-30-60-120) minutes postoperative, and in the second group, a significant decrease in (RBC), (PLT), (Hb) and (PCV) during the times (15-30-60) minutes postoperative. The count (WBC) showed no significant change in both groups, at the significance level P≤ 0.05. TXK protocol was superior to SXK protocol in producing faster onset of anesthesia, longer duration of anesthesia and analgesia with lower doses, and lower effects on clinical indicators and hematological parameters.